STANDARDIZATION: PERIOPERATIVE POINT OF CARE BEST PRACTICE - Shewchuk, Muriel (Operating Room Nurses Association of Canada Journal, 2014)
Standardization is used to develop, implement and sustain repetitive technical practices among team members. Standardization presumes personnel use a detailed, documented, well understood, consistent order and sequence details for initiating and progressing through a technical process. Standardization infers a common goal of safety, accuracy, efficacy, efficiency and quality. Personnel in Surgical Suites/Operating Rooms (OR’s) perform millions of single repetitive technical skills, each with a potential impact on patient outcome and team members. Individual diversity, when performing the details of each task, opens the door to increased error, patient risk, wasted time and interstaff frustration. Just imagine if industry allowed individual variances in processes.